Can the Right Crop Mix Reduce the Water Rebound Effect Following Improvements in Irrigation Efficiency? - Chai, Ying; Zhang, Haoran; Ma, Zilong; Pan, Su; Zhou, Jieqi (Frontiers in Water, 2022)
Water rebound has been recognized as a significant issue that reduces the effectiveness of irrigation efficiency improvement policies aimed at water conservation. However, there is an absence of quantitative analysis of the impact of crop mixes on the water rebound effect, and studies focusing on the heterogeneous effects of various climatic regions are scarce. Thus, this study aims to explore the effects of water rebound on irrigation efficiency improvements from the perspectives of crop mix and climatic region. First, we construct a double-layered moderating effect framework to incorporate the two interactive factors of crop mix and climatic region combined with two rebound mechanisms, cost reduction and increased revenue. Second, we conduct empirical analyses to test three hypotheses based on provincial-level data from 2003 to 2017 in China, which provides a unique empirical context wherein changes in the crop mix depend on factors other than the water-use policy. This paper takes advantage of the implementation of Rural Land Contracting Law since 2003 and Water Conservancy Key Counties Construction Program since 2009 to identify the effects of water rebound on irrigation efficiency improvements from the perspectives of crop mix and climatic region. We found that the water rebound effect was about 67.72%. Crop mixes involving higher proportions of non-grain crops were associated with higher levels of water conservation and less water rebound. Furthermore, non-grain crops in humid regions were more likely to experience water rebound than those in non-humid regions. Thus, given China's national strategy of food security, reducing the proportion of non-grain crops in humid regions will help to sustain agricultural water resources and conserve the environment.